Menelisik Kontribusi Artificial Intelligence Dalam Pemberitaan Injil di Lingkup Gereja Pentakostal - Sapdinator Saplirinata; Adi Ehut Lande (Pusat Studi Pentakosta Indonesia, 2026)
Nowadays, artificial intelligence (AI) has become a dominant paradigm in modern industry with its technological sophistication. The presence of AI has become a phenomenon in itself and many developed countries are competing to create their own versions of the most advanced AI. In fact, it could be said that this race to master AI will be a determining factor in future world leadership in terms of geopolitics, industry, and economics. Therefore, to keep up with the times, the church of God needs to know, understand, and use this AI so that it can maximize the calling and service. The purpose of this study is to examine the contribution of AI in the proclamation of the Gospel in the Pentecostal church. The use of descriptive qualitative methods and literature reviews is intended to be able to explain sharply and in detail the contribution of technology in building human civilization, describe the use of technology in the proclamation of the good news, and the contribution of AI to the proclamation of the Gospel today in the Pentecostal church. In conclusion, for the Pentecostal church, the existence of AI is considered to facilitate the proclamation of the good news, make it cheaper, make it more flexible, and is considered highly relevant.AbstrakPada masa kini, kecerdasan buatan (AI) sudah menjadi primadona dalam industri modern dengan kecanggihan teknologinya. Kehadiran AI ini sudah menjadi fenomena tersendiri dan banyak negara maju berlomba-lomba dalam menciptakan AI tercanggih versi mereka, bahkan boleh dibilang perlombaan penguasaan AI ini akan menjadi penentu dalam kepemimpinan dunia mendatang baik dari aspek geopolitik, indusrti, maupun ekonomi. Maka dari itu, agar tidak tertinggal, gereja Tuhan pun perlu untuk mengenal, memahami, dan menggunakan AI ini sehingga bisa memaksimalkan panggilan dan pelayanannya. Adapun tujuan penelitian ini ingin menelisik kontribusi AI dalam pemberitaan Injil di lingkup gereja bernuansa pentakostal. Penggunaan metode kualitatif deskriptif dan kajian literatur dimaksudkan agar mampu menjelaskan secara tajam dan terperinci terkait kontribusi teknologi dalam membangun peradaban manusia, mendeskripsikan penggunaan teknologi dalam pemberitaan kabar baik, juga kontribusi AI bagi pemberitaan Injil masa kini di lingkup gereja bernuansa pentakostal. Disimpulkan, bagi gereja pentakostal keberadaan AI diyakini mempermudah pemberitaan kabar baik, mempermurahnya, menjadikan lebih fleksibel, serta dianggap sangat relevan.